METAL AGE AND ITS PROBLEMS IN SOUTH KALIMANTAN - Sunarningsih Sunarningsih (Balai Arkeologi Kalimantan Selatan, 2013)
Abstract. Metal age in Indonesia is the period when humans were familiar with metalworking. In general, metaltools were used for either everyday or ritual purposes. However, there are also metal tools which are used asideofacts as well as technofacts. The results of a number of archaeological researches in South Kalimantanindicate that data of metal tools are very few. Therefore, the determination on the earliest use of metal tools andthe varieties of its use has not been comprehensively understood. This paper discusses a number of archaeologicalresearches in Kalimantan in the effort to identify problems related to metal culture. The research method used inthis study was descriptive and inductive reasoning. Data were collected by studying research reports of the Centrefor Archeology, Banjarmasin, literatures on metal culture in Indonesia as well as metal tools references of thecollection of Lambung Mangkurat Museum. The results showed that metal age sites in South Kalimantan aresettlements indicated by material cultures of fragments of iron tools or iron slag. Besides fragments of iron, neitherthe complete artefacts nor the chronology, have been identified yet.